Hybrid Theatre: An Adaptation of Performing Techniques in the Efforts to Preserve the Art of Theatre Performance Post COVID-19 - Andika Aziz Hussin; Addley Bromeo Bianus (Pejabat Karang Mengarang (UPSI Press), 2022)
The pandemic of COVID-19 and the Movement Control Order (MCO) have opened up the minds of local theatre players to be more creative in applying the suitable medium in showcasing their creative performances. Thus, emerged various forms of virtual theatre known as ‘online theatre’. No one ever imagined that theatre performances would be performed online but now, it is a practical approach in ensuring the sustainability of the theatre art itself. However, various questions arose about online theatre in Malaysia, such as, confusion with the understanding of the terms, forms and concepts of the performance. This study and writing is based on the online theatre performance—’Sel Akhir’ by the Seni Ceritera Association and King Lear by the KL Shakespeare Players (KLSP). The authors used observation and comparison methods to explain the approach used by these two presentations and propose to our Malaysian theatre players an adaptation method of online performance that suits the current capabilities and requirements, known as hybrid theatre.